Tapiola blue city: geographies and water imaginaries in Aarne Ervi’s urban proposal - Fernández-Vivancos González, Enrique (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2024)
In 1952, the finnish architect Aarne Ervi took charge of the review and subsequent development of the Tapiola Planning Plan, with the aim of converting the construction of this new city into a pilot project for the planned growth in the metropolitan area of ​​Helsinki. Considered a fundamental reference of rationalist urban planning and architecture of the second half of the 20th century in Finland, this assignment has largely contributed to making invisible the continuity in Ervi’s work of some of the approaches associated with organicism that the proposal initial contained. This article focuses on two of them, specifically its attention to the hydrology of the territory and the symbolic meaning of water in Finnish culture, as strategies for organizing and characterizing the public space of Tapiola. This approach aims to reveal, through Ervi’s work, how a careful look at the territory and the culture of the place allowed us to formulate a proposal that seeks to make compatible: environmental protection, socioeconomic development and urban growth.